2021
DOI: 10.1002/eat.23634
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the contingencies of self‐worth associated with eating disorder symptoms: The use of choice‐based conjoint analysis

Abstract: Objective Self‐worth contingent on shape/weight is a diagnostic criterion and key maintaining factor for eating disorders. However, the role of other contingencies of self‐worth (i.e., domains in which self‐worth is invested) is largely unknown. Moreover, research has relied on self‐ratings of contingency strength, which are subject to distortion through socially desirable responding and limited self‐awareness, and may have limitations in terms of ecological validity. To overcome these limitations, the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Studies have found that women with eating disorders often feel the need to be thin to maintain their self-worth (Granek 2007, Lampard et al 2013, Forrest et al 2020, while men may feel the need to be lean/fit and muscular (Drummond 2002, Björk et al 2012. Although recent research suggests that self-worth should not be limited solely to body shape and thinness (Rieger et al 2021), strong evidence in the literature indicates that individuals with eating disorders, both women and men, tend to focus their self-worth sources and conditions predominantly on their physical appearance. Based on these findings, it can be considered that an excessive focus on physical appearance and the selection of physical appearance as the primary source of selfworth may contribute to the development of eating disorders.…”
Section: Eating Disorders and Self-worthmentioning
confidence: 99%
“…Studies have found that women with eating disorders often feel the need to be thin to maintain their self-worth (Granek 2007, Lampard et al 2013, Forrest et al 2020, while men may feel the need to be lean/fit and muscular (Drummond 2002, Björk et al 2012. Although recent research suggests that self-worth should not be limited solely to body shape and thinness (Rieger et al 2021), strong evidence in the literature indicates that individuals with eating disorders, both women and men, tend to focus their self-worth sources and conditions predominantly on their physical appearance. Based on these findings, it can be considered that an excessive focus on physical appearance and the selection of physical appearance as the primary source of selfworth may contribute to the development of eating disorders.…”
Section: Eating Disorders and Self-worthmentioning
confidence: 99%
“…The face commonly represents our most distinguishing physical feature [ 39 ] and aberrations in face processing such as facial emotion recognition and interpreting expressions are observed in various psychopathologies including alexithymia, autism spectrum disorder, schizophrenia, and mood disorders [ 40 42 ]. Moreover, distortions in self-face perception are linked to body dysmorphic disorder and EDs [ 43 , 44 ], where the face is pivotal in attractiveness judgments [ 45 ]. Exploring multisensory mechanisms underlying self-face representation may contribute to an advanced aetiological understanding and interventions for EDs and related conditions.…”
Section: Introductionmentioning
confidence: 99%
“…EDs, such as anorexia nervosa and bulimia nervosa, are characterised by disturbed eating behaviours and attitudes driven by weight and shape concerns, typically focusing on body regions associated with adiposity (e.g., the abdomen, hips, and thighs) ( 15 ). Conversely, BDD is distinguished by a preoccupation with perceived defects in any body part, particularly the face ( 15 17 ), though the face can also be an area of concern in EDs ( 18 ). The accurate perception and representation of one’s body and face are fundamental to visual self-recognition, which is the ability to recognise one's appearance ( 19 ) and may be crucial for understanding body image disturbance in both EDs and BDD.…”
Section: Introductionmentioning
confidence: 99%